Biochemical Studies of Bacterial Sporulation and Germination XIV. Phospholipids in Bacillus megaterium - Bertsch, LeRoy L. (1969)
The principal phospholipids of Bacillus megaterium throughout the cycle of growth and sporulation were found to be phosphatidylglycerol, diphosphatidylglycerol, phosphatidylethanolamine, and a hitherto unidentified isomer of glycosaminyl-phosphatidylglycerol. Phosphatidylglycerol predominated during vegetative cell growth and then declined as spores developed, whereas diphosphatidylglycerol became more prominent during spore maturation. The latter phosphatide was relatively inaccessible in the vegetative cell and was more accessible in the spore, as judged by solvent extraction under various conditions.